2020
DOI: 10.1136/injuryprev-2020-043644
|View full text |Cite
|
Sign up to set email alerts
|

Ridesharing and motor vehicle crashes: a spatial ecological case-crossover study of trip-level data

Abstract: BackgroundRidesharing services (eg, Uber, Lyft) have facilitated over 11 billion trips worldwide since operations began in 2010, but the impacts of ridesharing on motor vehicle injury crashes are largely unknown.—MethodsThis spatial ecological case-cross over used highly spatially and temporally resolved trip-level rideshare data and incident-level injury crash data for New York City (NYC) for 2017 and 2018. The space-time units of analysis were NYC taxi zone polygons partitioned into hours. For each taxi zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…Whereas much of the focus of the report is on documenting the extent of sexual assault occurring in Uber rides and by Uber drivers, Uber went further in the report to investigate the extent of motor vehicle fatalities involving Uber. They find that the rate of traffic fatalities involving an Uber driver, per vehicle mile travelled, is actually half of the rate in the total population [24]. Hence, whereas we find that traffic fatalities, including weekend/ holiday as well as alcohol-related fatalities, increased in population dense and urban centered areas, the increases do not necessarily involve Uber drivers.…”
Section: Plos Onecontrasting
confidence: 69%
See 1 more Smart Citation
“…Whereas much of the focus of the report is on documenting the extent of sexual assault occurring in Uber rides and by Uber drivers, Uber went further in the report to investigate the extent of motor vehicle fatalities involving Uber. They find that the rate of traffic fatalities involving an Uber driver, per vehicle mile travelled, is actually half of the rate in the total population [24]. Hence, whereas we find that traffic fatalities, including weekend/ holiday as well as alcohol-related fatalities, increased in population dense and urban centered areas, the increases do not necessarily involve Uber drivers.…”
Section: Plos Onecontrasting
confidence: 69%
“…To explain the lack of a main effect of Uber's availability yet significant interaction associations with population density and urbanicity, we first note that Uber recently released its first ever Safety Report [24]. Whereas much of the focus of the report is on documenting the extent of sexual assault occurring in Uber rides and by Uber drivers, Uber went further in the report to investigate the extent of motor vehicle fatalities involving Uber.…”
Section: Plos Onementioning
confidence: 99%
“…In several studies in the United States (8,13,18) and the United Kingdom (30), authors found Uber's presence was not associated with crash fatalities; but authors of the studies from Brazil (25), Chile (26)(27)(28), South Africa (29), and 2 from the United States (15,22) found the presence of ride-hailing services were negatively associated with crash fatalities. In another analysis of US cities (19) and in a small-area study in New York City (20), researchers found positive relationships for injury and fatal crashes. Attention has turned in recent years to understanding how different researchers using comparable analytic methods, sometimes in the same geographic settings, could arrive at such divergent results.…”
Section: A Decade Of Ride-hailing Service; Half a Decade Of Researchmentioning
confidence: 97%
“…Brazil and Kirk's work is an instructive example of the state of the science, because most studies published in the intervening 5 years have used similar data and methods to examine similar outcomes. Most were set in the United States (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), apart from a handful of others conducted in Brazil (25), Chile (26)(27)(28), South Africa (29), Spain (30), and the United Kingdom (31). Other authors also examined associations with overall injury or fatal crash incidence (13, 15, 16, 18-23, 25-27, 29, 31) or with alcohol-involved injury or fatal crash incidence (10-15, 18, 22, 24, 26, 27, 30).…”
Section: A Decade Of Ride-hailing Service; Half a Decade Of Researchmentioning
confidence: 99%
See 1 more Smart Citation